Measuring the Impact of Human Resource Management Practices on Organizational Performance with the Mediating Role of Supply Chain Performance between Them in Saudi Industrial Large Organizations - Albahussain, Sami Abdullah; Elgaraihy, Wael Hassan; Mobarak, Abdel-Kader Mohamed (Archives of Business Research, 2016)
The main objective of this study is to measure the impact of human resource management practices on organizational performance of the Saudi industrial organizations, with analysing the mediating role of supply chain performance in the relationship between human resource management practices and organizational performance. Study population included all Saudi organizations registered in Commerce Industrial Chamber in the Eastern Province. Two hundred seventy-four (274) questionnaires were distributed. The number of correct questionnaires was 218, representing 79.6% of the total number of distributed questionnaires. The study results confirmed the existence of a significant positive impact of human resources management practices on the efficiency of supply chain performance and organizational performance. The results of this study revealed that the HR practices affect the efficiency and effectiveness of supply chain performance, and then the organizational performance. The results also confirmed that the supply chain performance plays the mediating role in that relationship. Therefore, it is essential that Saudi organizations try to exert endeavors to implement exclusive ranges of human resource management practices to assist them in achieving an excellent level of organizational performance.